FATORES DE SOLO E CLIMA QUE AFETAM O RENDIMENTO MÉDIO DO MILHO NAS REGIÃ•ES HOMOGÊNEAS DA PARAÃBA - Rocha Filho, J. V. C.; Alcoforado, C. B.; Pessoa da Costa, G. T.; Tejeda, H. R. (REVISTA DE AGRICULTURA, 2020)
FATORES DE SOLO E CLIMA QUE AFETAM O RENDIMENTO MÉDIO DO MILHO NAS REGIÃ•ES HOMOGÊNEAS DA PARAÃBA